Reformulación del modelo Linda para compartir conocimiento en sistemas multi-agente - Tamargo, Luciano H. (2006)
The aim of this work is to analyze the knowledge interchange on multi-agent systems using shared knowledge areas. The project involves the analysis and reformulation of some aspects of the Linda model, adding new model level features. This work proposes the idea of distributed tuples spaces, offering the possibility of coexistence among different tuples spaces with distinct features, being stored in remote sites. This distributed model requires the definition of new operations whose domain and range are tuples spaces, and the formulation of access constraints for the agents